Heirs’ Liability for State Losses Arising from a Deceased Corruption Offender under Islamic Inheritance Law - Rodliyah, Nunung; Lintang, Dheanilla Esa (Corruptio, 2024)
Corruption is an extraordinary crime that often leaves unresolved legal consequences when the perpetrator dies before serving their sentence, raising the question of whether heirs are responsible for settling resulting state losses. This study employs normative legal research through literature review to examine the compatibility between Islamic inheritance principles and the civil liability imposed on heirs in such cases. The findings show that Islamic inheritance law recognizes heirs’ obligation to settle the deceased’s debts, including those from unlawful acts, but strictly within the limits of the inherited estate. Thus, while heirs can be held accountable for corruption-related debts, their liability is confined to the value of the assets they receive. This highlights the importance of integrating religious norms and positive law to ensure fair and effective recovery of state losses after the perpetrator’s death.